HUBUNGAN DISMENORE PRIMER DENGAN PRESTASI BELAJAR MAHASISWI PROGRAM STUDI ILMU KOMUNIKASI FISIP UNUD - Putra, Made Edi Pramana; Pramitaresthi, I Gusti Ayu; Yanti, Ni Putu Emy Darma (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020, 2020)
Most young women experience primary dysmenorrhea. The primary dysmenorrhea affect activity especially learning. Disrupted learning activities will affect women's learning achievement. The purpose of this study was to determine the relationship between primary dysmenorrhea and the learning achievement of Communication Study Program students FISIP Unud. The design of the research is a correlative analytics through a cross sectional approach with retrospective data collection. Respondents were 65 female students of 2016-2018 who experienced primary dysmenorrhea??. The sampling used the proportionate stratified random sampling. Analysis used are frequency tables for univariate and Gamma Correlation test for bivariates (? = 0,05). Data obtained results from 65 female students who experienced primary dysmenorrhea had the most moderate dysmenorrhea as many as 37 female students (56.9%) and at most received the title of learning achievement with praise of 57 students (87.7%). The Gamma Correlation test results show that p <0.05 (p = 0.001) and the correlation value (r) = -1,000. Based on this, it can be concluded that there was a relationship between primary dysmenorrhea and the learning achievement of Communication Study Program students FISIP Unud, with a negative relationship direction that is the higher the primary dysmenorrhea, the lower the learning achievement and vice versa with the power of correlation was statistically very strong. It is expected that students will be able to choose the right effort to improve learning achievement.